Exploring knowledge of first aid in epistaxis—25 years on - Henry Dunne; Michael Abouabdallah; Joseph Roscamp; Samuel Birks; Kate Mcgibbon; Sam Dewhurst; David Strachan; Rishi Sharma (PLoS ONE, 2025)
Background Epistaxis is the most common acute disorder managed by ENT services. A 1998 survey (Strachan and England) demonstrated widespread ignorance of correct first aid amongst the public with only 11% of respondents applying correct first aid techniques. Here we repeated and expanded the 1998 study to investigate whether understanding of correct first aid in epistaxis amongst the public and emergency department staff has improved in the last 25 years. Methods Posters with links to surveys were displayed in ED waiting rooms, anticoagulation clinics and ED staff rooms in multiple UK centres. Responders were asked three first aid questions: pinch position, head position, and plugging nostrils. A prospective audit was carried out in a single centre over four weeks recording the first aid was being applied at the point of ENT review for patients referred with epistaxis. Findings 129 members of public responded. 83% do not have correct first aid technique including 77% of those on anticoagulants or aspirin. 116 ED staff responded. 64% do not use correct first aid. Over four weeks 19 patients were referred to ENT with epistaxis and of these, nine were bleeding at the point of ENT review. Adequate first aid was not being applied in 56% of those cases. Conclusions Despite the morbidity of epistaxis, and the simplicity of first aid steps, there is concerning lack of understanding amongst the public and ED staff. Education (particularly for staff and the anticoagulated) may reduce emergency attendance in epistaxis patients.